Oxidative stress and antioxidant parameters in neutropenic patients secondary to chemotherapy - Dogantekin, Akif; Gurel, Ali; Ustundag, Bilal; Ilhan, Selcuk; Elkiran, Emin Tamer (Professional Medical Publications, 2016)
Objective: Neutropenia is a serious adverse event that necessitates dosage reduction in patients receiving chemotherapy. In this study, we evaluated the oxidative stress and antioxidant parameters in neutropenic patients after chemotherapy both during the neutropenic period and after successful treatment of neutropenia with filgrastim. Methods: We studied paraoxonase (PON1), arylesterase (ARE), malondialdehyde (MDA), high-density lipoprotein (HDL), lactate dehydrogenase (LDH), and alkaline phosphatase (ALP) in addition to routine biochemical and hematologic parameters. SPSS 12.0 was used for statistical evaluation of data (SPSS, Chicago, IL, USA). Results: In our study, PON1, HDL, and LDH levels during the period of active neutropenia were statistically significantly higher than these levels were after resolution of neutropenia (P<0.05); MDA and ALP levels were statistically significantly lower during the period of active neutropenia (P<0.05). Conclusions: Overall, free oxygen radicals (FOR) were increased and antioxidant parameters were decreased with resolution of neutropenia. This is probably due to FOR produced by the increased number of neutrophils rather than tumor burden.
Keywords: Antioxidant; Malondialdehyde; Neutropenia secondary to chemotherapy; Oxidative stress; Paraoxonase